THE EFFECT OF DIGITAL MEDIA ON THE SOCIO-EMOTIONAL DEVELOPMENT OF CHILDREN AGED 5–6 YEARS - Umianita Risca Wulandari; Dian Kumalasari (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2026)
The increasing use of digital media in early childhood is feared to impact children's ability to manage emotions, interact socially, and understand the behaviour of others. The study used a quantitative correlational design with 45 parents of children aged 5–6 years old as respondents. The study was conducted from June to July 2025 at Permata Pelangi Kindergarten, Kediri. The research instruments consisted of a digital media use questionnaire and a social-emotional development questionnaire adapted from SEAM, with a Cronbach's Alpha reliability of 0.87. Univariate and bivariate analyses were performed using the Chi-square test. The results showed that most children used digital media for 1–3 hours per day, and the majority had good social-emotional development. The characteristics of mothers, who were predominantly of productive age and had secondary education, potentially influenced their child's support patterns during digital media use. The analysis showed no significant relationship between screen time and child development (p 0.05). Although descriptively, children with longer screen time tended to have adequate development, this trend was not statistically significant. This indicates that the duration of digital media use is not the primary factor determining a child's social and emotional development. Other factors such as content quality, parenting styles, parental support, and children's social activities at school are thought to play a larger role.